'The (charitable) pantry is bare': a critical discourse analysis of Christmas food hamper programs in Canada. Issue 1 (2nd January 2021) - Smith-Carrier, Tracy
ABSTRACT: At all times, but especially during the Christmas season, Canada's reliance on the charitable food sector is markedly apparent. This paper examines, using the Discourse-Historical Approach (DHA) of Critical Discourse Analysis (CDA), the historical, contextual, referential and discursive themes emerging in major news stories about the provision and receipt of Christmas food hampers in Canada. Several themes emerged: descriptions of deservingness in the uneven apportionment of charitable assistance; the assumed adequacy of food charity in the wake of increasing need; the asymmetrical power relations and emotional costs/rewards of food charity; and expectations of gratitude and preferred behaviors for those in charitable receipt. What was absent in these data was any mention of human rights, or dialogue about evidence-informed solutions that might effectively alleviate Canada's poverty and food insecurity problems. The discussion section considers how income security can be realized in Canada through a basic income guarantee, grounded in human rights infrastructure.